An Iterative Thresholding Method for the Minimum Compliance Problem (Communications in Computational Physics, 2023)
In this paper, we propose a simple energy decaying iterative thresholdingalgorithm to solve the two-phase minimum compliance problem. The material domain is implicitly represented by its characteristic function, and the problem is formulated into a minimization problem by the principle of minimum complementaryenergy. We prove that the energy is decreasing in each iteration. Two effective continuation schemes are proposed to avoid trapping into the local minimum. Numericalresults on 2D isotropic linear material demonstrate the effectiveness of the proposedmethods.
Keywords: Minimum compliance; convolution; thresholding; linear elasticity.